If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(1.75+.7n)-2n=2(1.75+.7n-1)-4.8n
We move all terms to the left:
3(1.75+.7n)-2n-(2(1.75+.7n-1)-4.8n)=0
We add all the numbers together, and all the variables
3(.7n+1.75)-2n-(2(.7n+0.75)-4.8n)=0
We add all the numbers together, and all the variables
-2n+3(.7n+1.75)-(2(.7n+0.75)-4.8n)=0
We multiply parentheses
-2n+3n-(2(.7n+0.75)-4.8n)+5.25=0
We calculate terms in parentheses: -(2(.7n+0.75)-4.8n), so:We add all the numbers together, and all the variables
2(.7n+0.75)-4.8n
We add all the numbers together, and all the variables
-4.8n+2(.7n+0.75)
We multiply parentheses
-4.8n+2n+1.5
We add all the numbers together, and all the variables
-2.8n+1.5
Back to the equation:
-(-2.8n+1.5)
n-(-2.8n+1.5)+5.25=0
We get rid of parentheses
n+2.8n-1.5+5.25=0
We add all the numbers together, and all the variables
3.8n+3.75=0
We move all terms containing n to the left, all other terms to the right
3.8n=-3.75
n=-3.75/3.8
n=-1/1.01333333333
| 1-7a=-11-4a | | 4/8=x/18 | | -x-1=x-15 | | (6x-3)-15=42 | | (X+15)+4x=180 | | 3x+2x–5=5+4x+x | | 4a+5=13+3a | | 87m+21=63 | | p2+300p-60000=0 | | 2x+12+2x+60=180 | | 2x^-13x+11=0 | | (2x+7)+63=90 | | 5.5x-2.5=4x | | 12x^2-9x-12=0 | | 92+(7x-52)=180 | | 4(x-3)-3x+1=13 | | 125/100=100/a | | 4x+1−1x=1 | | 10x=24x+103748 | | 12x-7+5x=8(2x+1)=x-8 | | 2/3=z/15 | | x2+400x-60000=0 | | (41/180)*21.99=x | | 2x-28=368 | | -2=2(w+5)-4w | | 3(0.7n+0.25)-2n=7(0.7n+0.25-1)-4.8n | | (x-15)+(4x)=180 | | |7x+4|+12=9 | | (x-5)+(4x)=180 | | 16−2r=−3r+6r+116 | | 10^5x=1.25 | | 3t^2−3t+1=0 |